2001
DOI: 10.1074/jbc.m104324200
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Thiolate Anion Is an Intermediate in the Formation of Albumin-S–S-Homocysteine

Abstract: An elevated concentration of plasma total homocysteine is an independent risk factor for cardiovascular disease. Greater than 80% of circulating homocysteine is covalently bound to plasma protein by disulfide bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
173
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(177 citation statements)
references
References 39 publications
4
173
0
Order By: Relevance
“…Consistent with this suggestion are the observations that S-Hcy-albumin and NHcy-albumin account for most (Ͼ90%) of S-linked and N-linked Hcy, respectively, present in human plasma protein and for Ͼ90% of total plasma Hcy (22,26,28). In addition to S-Hcyprotein (26,31,32) and N-Hcy-protein (12, 13, 26 -28), Hcy exists in circulation as free reduced Hcy (31), Hcy-thiolactone (24,25), and disulfide forms with low molecular weight thiols (31). Of these, Hcy-thiolactone (10, 17, 21-23, 26, 28, 29) and free reduced Hcy (37), which comprise 1.4 (24,25) and 2% (31) of plasma total Hcy, respectively, have been suggested to be the deleterious forms of Hcy.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Consistent with this suggestion are the observations that S-Hcy-albumin and NHcy-albumin account for most (Ͼ90%) of S-linked and N-linked Hcy, respectively, present in human plasma protein and for Ͼ90% of total plasma Hcy (22,26,28). In addition to S-Hcyprotein (26,31,32) and N-Hcy-protein (12, 13, 26 -28), Hcy exists in circulation as free reduced Hcy (31), Hcy-thiolactone (24,25), and disulfide forms with low molecular weight thiols (31). Of these, Hcy-thiolactone (10, 17, 21-23, 26, 28, 29) and free reduced Hcy (37), which comprise 1.4 (24,25) and 2% (31) of plasma total Hcy, respectively, have been suggested to be the deleterious forms of Hcy.…”
supporting
confidence: 72%
“…3), the exchange with cysteine was Ͻ20% complete (not shown). Thiol-disulfide exchange reactions between albumin-Cys 34 -SH and cystine, homocystine, or Cys-S-S-Hcy disulfide are known to be slow, being about 20% or less complete in 4 h (32,36).…”
mentioning
confidence: 99%
“…[23][24][25] Furthermore, we recently demonstrated that when homocysteine and cysteine are simultaneously incubated with human albumin, Ϸ4-fold more homocysteine than cysteine becomes protein bound. 11 To identify the region(s) of fibronectin to which homocysteine binds, a limited trypsin digestion of fibronectin that had been labeled with radioactive homocysteine was carried out. Several of the resulting protein fragments that contained the radioactive homocysteine were sequenced by using LC/MS.…”
Section: Discussionmentioning
confidence: 99%
“…26) The remaining sulfhydryl groups are freely accessible (mercaptalbumin) and represent the largest fraction of free thiols in blood. Mercaptalbumin and probably also part of albumin forming mixed disulfides are able to bind nitric oxide and metal ions such as Ag ϩ , Hg 2ϩ , and Au ϩ as well as homocysteine 27) and several drugs. Among the latter are bucillamine derivatives, 28) aurothiomalate, 29) auranofin, 30) D-penicillamine, 31,32) captopril, 32,33) ethacrynate, 34) and cisplatin (which also binds to methionine residues).…”
Section: Ligand Bindingmentioning
confidence: 99%